Futuro de las comunidades campesinas. Pacaraos 40 años despues - Montoya Rojas, Rodrigo (2005)
this article presents the results obtained in field work in the year 2002 and it campares structural and cultural aspects of the institutions and inhabitants of the Peasant Commning of Pacaraos registered previously in 1962. Aften presenting sythetically the academic vicissitudes of the anthropological expedition of a group of students from San Marcos in this same Andean space,it examines and analyzes the changes taken place in the agricultural educational, local governmental and health dimensions and the limits of thye functionality of a peasant commmnity. Finally, it proposes a set of ideas for action so that the authotities of Pacaraos can find a way out of the current crisis in which they live